2016
DOI: 10.1080/14686996.2016.1172024
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of delafossite-type CuAlO2 fibers with Eu substitution for Al cations

Abstract: CuAlO2 has been examined as a potential luminescent material by substituting Eu for Al cations in the delafossite structure. CuAlO2:Eu3+ nanofibers have been prepared via electrospinning for the ease of mitigating synthesis requirements and for future optoelectronics and emerging applications. Single-phase CuAlO2 fibers could be obtained at a temperature of 1100 °C in air. The Eu was successfully doped in the delafossite structure and two strong emission bands at ~405 and 610 nm were observed in the photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Synthesis of delafossites in nanophase such as nanoparticles, nanowires, nanoplates and investigating the particle size effect on the properties of these materials is another interesting field which is currently being explored. Eu 3+ doped CuAlO 2 single phase nanofibers prepared via an electrospinning technique show strong photoluminescence spectra with emission bands at 405 and 610 nm due to the intrinsic near-band-edge transition of CuAlO 2 and the f-f transition of the Eu 3+ activator respectively [25]. Nanoplates of CuGaO 2 synthesized via low temperature hydrothermal method exhibited a blue emission at room temperature and free exciton emission at low temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of delafossites in nanophase such as nanoparticles, nanowires, nanoplates and investigating the particle size effect on the properties of these materials is another interesting field which is currently being explored. Eu 3+ doped CuAlO 2 single phase nanofibers prepared via an electrospinning technique show strong photoluminescence spectra with emission bands at 405 and 610 nm due to the intrinsic near-band-edge transition of CuAlO 2 and the f-f transition of the Eu 3+ activator respectively [25]. Nanoplates of CuGaO 2 synthesized via low temperature hydrothermal method exhibited a blue emission at room temperature and free exciton emission at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…data. Experimental pressure volume data obtained by the Rietveld refinement [59] of XRD data for the low pressure phase when fitted to 3rd order Birch-Murnaghan equation of state results in ambient pressure bulk modulus as 154 (25) and 156(2.8) GPa with their pressure derivative of bulk modulus as 4.8(0.5) and 5.3(0.5) for CuLaO2 and CuCrO2 respectively. It is to be noted here that bulk modulus and pressure derivative of bulk modulus are highly correlated [75].…”
Section: High Pressure Studiesmentioning
confidence: 99%
“…Due to the rather large range of possible stable configurations, it is not surprising that delafossites exhibit a significant richness in properties and potential applications. Several important technological applications have been proposed for members of this family, such as electrodes for hydrogen production by photo-electrochemical water splitting 6 7 , as luminescent materials 8 , in solar cells 9 10 11 , for thermoelectricity 12 13 14 15 , as possible transparent supercondutors 16 , etc. Recently, it was also found that delafossite PtCoO 2 behaves like a nearly free-electron system, turning this surprising 5d transition-metal system in the most conductive oxide known 17 .…”
mentioning
confidence: 99%
“…In fact, Eu 3+ ions, also possess a series of visible emission lines that originate from the 5 D 0 and 5 D 1 multiplets with good color-tuning properties [30,72,82], that make them very interesting for lightening applications. In fact, Eu-doped nanofiber mats have already been tested in realistic LED devices [32,34] and Eu 3+ is probably the mostly studied rare earth ion in nanofiber matrixes [1,13,19,29,30,32,34,35,37,41,42,45,47,48,51,[53][54][55]61,62,67,68,76,[79][80][81][82]84,[86][87][88][89]91,101,112] including some nanobelt structures [72] and hollow structures [82]. In most of these cases, diameter of the nanofibers was less than 300 nm, with a few exceptions [35,42,76].…”
Section: Electrospun Rare Earth Doped Crystal Fibers 41 Electrospun Fibers With Stokes Emissionsmentioning
confidence: 99%